Gamifikasi dalam Pembelajaran Akuntansi untuk Pemuda: Solusi Inovatif atau Sekadar Hiburan? - Klaudia, Sura (STIE Atma Bhakti, 2025)
This study aims to analyze the effectiveness of gamification in accounting education for youth, particularly students aged 17–25. Gamification is a game-based learning strategy believed to enhance engagement and learning motivation. This research employs a descriptive quantitative approach by distributing questionnaires to 120 respondents who have participated in gamified accounting learning, such as using applications like Kahoot!, Quizizz, and game-based accounting simulations. The results show that 78% of respondents felt more motivated to learn accounting through the gamification approach. Additionally, 64% of respondents stated that their understanding of basic accounting concepts improved, while 60% found it easier to retain the learning material. On the other hand, around 25% of respondents tended to view gamification merely as entertainment, without paying attention to the substance of the material presented. These findings indicate that gamification has potential as an innovative and relevant learning method for the characteristics of today’s younger generation. However, its effectiveness largely depends on game design, content integration, and the teaching approach employed by educators. Therefore, an appropriate implementation strategy is necessary to ensure that gamification not only serves as a form of entertainment but also strengthens conceptual and practical understanding of accounting.